2016
DOI: 10.1016/j.bandl.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The neural underpinnings of reading skill in deaf adults

Abstract: We investigated word-level reading circuits in skilled deaf readers (N=14; mean reading age=19.5years) and less skilled deaf readers (N=14; mean reading age=12years) who were all highly proficient users of American Sign Language. During fMRI scanning, participants performed a semantic decision (concrete concept?), a phonological decision (two syllables?), and a false-font control task (string underlined?). No significant group differences were observed with the full participant set. However, an analysis with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…Alternately, other studies have not shown clear use of phonological processing in deaf readers [78][79][80][81]. As a result, some researchers believe phonology might be bypassed by focusing on morphemes in the orthography of text.…”
Section: Phonological Processing In Word Recognitionmentioning
confidence: 98%
“…Alternately, other studies have not shown clear use of phonological processing in deaf readers [78][79][80][81]. As a result, some researchers believe phonology might be bypassed by focusing on morphemes in the orthography of text.…”
Section: Phonological Processing In Word Recognitionmentioning
confidence: 98%
“…In the Bélanger et al (2012) experiment, the size of masked phonological priming was not predictive of the reading level in deaf readers. Similarly, in a recent fMRI study comparing skilled and less skilled deaf readers, Emmorey, McCullough, and Weisberg (2016) found that reading ability was not correlated with off-line measures of phonological awareness nor with neural activity during a phonological (syllable counting) task. In the current study, we make use of the variability of reading levels existing amongst congenitally deaf participants to analyze the relationships between their score in standardized reading tests and performance during the task as well as the size of the ERP effects.…”
Section: Introductionmentioning
confidence: 95%
“…Because phonological processing plays a central role in read acquisition for hearing readers, much research on deaf readers has focused on whether or not they activate phonological representations when reading and whether such abilities determine reading skills (Daigle & Armand, 2008;Hanson & Fowler, 1987;Perfetti & Sandak, 2000). While these questions still dominate the field (Emmorey, McCullough, & Weisberg, 2016;Hirshorn, Dye, Hauser, Supalla, & Bavelier, 2015), no consensus exists about the role of phonological processes in deaf readers, likely due to the heterogeneity of the population and to methodological differences across studies: some find phonological activation in deaf readers (Daigle & Armand, 2008;Transler, Gombert, & Leybaert, 2001) while others do not (Bélanger, Baum, & Mayberry, 2012;Bélanger, Mayberry, & Rayner, 2013;Cripps, McBride, & Forster, 2005;Waters & Doehring, 1990).…”
mentioning
confidence: 99%